HISTOPATHOLOGY OF LEAF SPOT OF SESAME (SESAMUM INDICUM L.) CAUSED BY PSEUDOMONAS SYRINGAE PV. SESAMI - S. S. Firdous; R. Asghar; G. Murtaza (Journal of Animal and Plant Sciences, 2014)
Pseudomonas syringae pv. sesami,the causal agent of bacterial leaf spot of sesame is responsible for sesame production constraintsduring monsoon season in Pakistan. In the present study, mode of infection of causal bacterium was conducted in susceptible genotype to elucidate the process of infection within host tissues. Bacterium was identified as dark blue masses in infected tissues using toluidine blue O. Results showed that pathogencolonized substomatal and intercellular spaces of the spongy parenchyma cells when initial water soaking symptoms developed at 2-3 days after inoculation. Upon water soaking progressed, disruption of mesophyll cells occurred, mesophyll tissues were surrounded by bacterium followed by thinning and disruption of the cell walls. Later, when bacterial cells increased in space previously occupied by mesophyll cells, there were empty spaces without any differentiation of tissues. Bacterium did not occur in vascular bundles (tracheary elements) of leaf and stem, but some phloem tissues of stem sections were found infected. It was concluded that damage chloroplast was might be due to chlorosis or necrosis inducing toxins and toxins played a crucial role in pathogenesis of Pseudomonas syringae pv. sesami in sesame plant.
Keywords: Pathogenesis; leaf spot; sesame; light microscopy